A novel multi-LDPC-NPPM modulation coding scheme for satellite ground laser communications - Jing Liu; Qi Zhang; Qinghua Tian; Bo Liu; Ying Tao; Yufei Shen; Dong Chen; Houtian Wang; Feng Tian; Naijin Liu; Xiangjun Xin (2016 15th International Conference on Optical Communications and Networks (ICOCN), 2016)
An efficient modulation and coding scheme combined with multiple LDPC codes and PPM modulation is proposed to mitigate the effect of atmospheric turbulence, which can have an unfavorable impact on the reliability of the communication link in the laser channel of the integration network of satellite and ground. The research is mainly about the reliability of the communication link under different orders and parameters of the PPM modulation. The result shows that it can effectively enhance the link reliability if the system uses the scheme of 8PPM and 1/2 code rate binary LDPC coding under different turbulent intensity. Comparing and analyzing the scheme of binary and multiple LPDC coding system, we found that the scheme combined with the multiple LDPC codes and PPM modulation and coding is more efficient than binary LDPC codes related programs.